Penerapan Pola Pengelolaan Keuangan Badan Layanan Umum (PPK-BLU) Pada Program Kesehatan Jiwa Masyarakat Puskesmas di Kabupaten Sleman - Karmijono Pontjo Widianto; Laksono Trisnantoro; Ratna Siwi Padmawati (Jurnal Kebijakan Kesehatan Indonesia, 2015)
Background: The decision of the Minister of Home Affairs No. 61 of 2007 on Technical Guidelines for Financial Manage- ment of Public Service Board seems to bring another option in the management of health centers which have existed as a Technical Implementation Unit (UPT) oh health department. The entire budget for health centers through the health departmen is able to follow the system of Financial Management of Re- gional Public Service Agency (PPK-BLUD) that provides flex- ibility in the implementation of the budget, including the revenue and expenditure management, cash management, and pro- curement of goods / services, and gives opportunity to hire a professional/non-civil servants and gives the opportunity for a performance based remuneration. Promotive and preventive health centers functions to encourage community empower- ment. That function is realized in each program activity called Public Health Efforts (SMEs); one of which is the Community Mental Health program (Keswamas). Objective: To describe the impact of the financial manage- ment of health centers using PPK-BLUD in the implementation of the SME program, in this case the community mental health program. Methods: This study used a case study design and descrip- tive analysis. Results: (1). There is no difference in principle on program management Keswamas before and after the BLUD. (2) The type of community mental health program activities carried out by the health center after BLUD status is the same as before the status as BLUD (3). Budgeting activities of community mental health programs in health centers after the BLUD status is the same as before the BLUD status (4). Human resources in- volved in the implementation of community mental health pro- grams in health centers after the BLUD status is as the same as before the BLUD status (5). The involvement of members of the management team is not specifically for community mental health program, but also other programs at the health center. Conclusion: There is no difference in the management of health centers in Sleman after PPK-BLUD, because not all of the flexibility or independence as PPK-BLUD is utilized by health centers and health authorities to create activities / new, more innovative programs and to solve existing health problems. An understanding of the PPK-BLUD is adequate but not encour- age health authorities and health centers to create a more innovative activities in solving the problems that occur. Knowl- edge and understanding of the PPK-BLUD supported by the courage to innovate is essential for health centers and health department leaders in order to take advantage of being PPK-BLUD to improve the quality of public services in order to improve the health of society. Management of health centers with PPK-BLUD is needed to provide flexibility of budget man- agement in the era of the National Health Insurance. Latar Belakang: Keputusan Menteri Dalam Negeri Nomor 61 tahun 2007 tentang Pedoman Teknis Pengelolaan Keuangan Badan Layanan Umum Daerah yang seolah-olah memunculkan pilihan lain dalam hal pengelolaan puskesmas yang selama ini berstatus sebagai Unit Pelaksana Teknis (UPT) dinas kesehatan. Seluruh penganggaran puskesmas yang selama ini melalui dinas kesehatan, menjadi dapat mengikuti sistem Pola Pengelolaan Keuangan Badan Layanan Umum Daerah (PPK-BLUD) yang memberikan fleksibilitas dalam rangka pelaksanaan anggaran, termasuk pengelolaan pendapatan dan belanja, pengelolaan kas, dan pengadaan barang/jasa serta diberikan kesempatan untuk mempekerjakan tenaga profesional non PNS dan kesem- patan pemberian imbalan jasa kepada pegawai sesuai dengan kontribusinya. Fungsi puskesmas promotif dan preventif yang berorientasi pada pemberdayaan masyarakat. Fungsi tersebut diwujudkan dalam setiap kegiatan program Upaya Kesehatan Masyarakat (UKM); salah satunya adalah program Kesehatan Jiwa Masyarakat (Keswamas). Tujuan: Menggambarkan dampak pengelolaan keuangan pus- kesmas dengan PPK-BLUD pada pelaksanaan program UKM dalam hal ini program kesehatan jiwa masyarakat Metode: Penelitian ini menggunakan rancangan studi kasus dan analisis deskriptif. Hasil: (1). Belum ada perbedaan pada pengelolaan program Keswamas sebelum dan setelah Era BLUD. (2) Jenis kegiatan program kesehatan jiwa masyarakat yang dilaksanakan oleh puskesmas setelah berstatus BLUD bertambah dibanding sebelum berstatus sebagai BLUD (3). Penganggaran kegiatan program kesehatan jiwa masyarakat di puskesmas setelah berstatus BLUD sama seperti sebelum berstatus BLUD (4). SDM yang terlibat dalam pelaksanaan kegiatan program kese- hatan jiwa masyarakat pada puskesmas setelah berstatus BLUD sama seperti sebelum berstatus BLUD (5). Keterlibatan anggota Tim sebagai pengelola kesehatan jiwa masyarakat tidak secara khusus menangani program namun juga menjalan- kan program lain di puskesmas. Kesimpulan: Belum ada perbedaan pengelolaan puskesmas di Kabupaten Sleman setelah diterapkan PPK-BLUD, karena belum semua keleluasaan atau kemandirian yang diberikan se- bagai PPK-BLUD dimanfaatkan oleh puskesmas maupun dinas kesehatan untuk menciptakan kegiatan/program baru yang lebih inovatif dan dapat menyelesaikan permasalahan kesehatan yang ada. Pemahaman tentang PPK-BLUD telah cukup namun belum mendorong dinas kesehatan dan puskesmas untuk berani menciptakan kegiatan yang lebih inovatif dalam menyelesaikan permasalahan yang terjadi. Pengetahuan dan pemahaman tentang PPK-BLUD yang didukung dengan keberanian berino- vasi sangat penting bagi pimpinan puskesmas dan dinas kese- hatan sebagai pembina puskesmas, agar dapat memanfaatkan status sebagai PPK-BLUD untuk meningkatkan mutu pelayanan pada masyarakat dalam rangka meningkatkan derajat kesehatan masyarakat. Pengelolaan puskesmas dengan PPK-BLUD sa- ngat dibutuhkan untuk memberikan kemudahan pada puskes- mas dalam pengelolaan anggaran dalam era Jaminan Kesehat- an Nasional.